Expanding the web: The case against net neutrality - Matthew Lesh (Institute of Economic Affairs (IEA), 2022)
Net neutrality is the principle that internet service providers (ISPs) should treat all web traffic equally. This means, in general, that ISPs may not block, slow down or speed up the transmission of any content or services. This is meant to promote an 'open internet': allowing users to access all content and services while ensuring low barriers to entry for innovative and new web applications. The UK's net neutrality rules derive from the European Union's Open Internet Access Regulation 2015, which came into force in 2016 and has been retained in UK law post-Brexit. These rules mandate net neutrality with exceptions for technical, security and legal requirements. Prior to the EU regulation, the UK relied on competition between ISPs, transparency and self-regulation to safeguard an open internet. This arrangement was acknowledged at the time, by the government, Ofcom and independent reviewers, to be effective. Acting of its own accord, the UK is unlikely to have introduced net neutrality regulations independently of the EU. Net neutrality rules limit the ability of ISPs to: (1) effectively manage traffic when the network is congested; (2) develop innovative offerings for consumers and emerging technologies; or (3) reach deals with major content providers, such as Netflix, to contribute to network maintenance and expansion in exchange for priority access. There is evidence that net neutrality reduces investment in telecommunications infrastructure. In addition to harming consumers, this undermines the government's gigabit broadband and 'levelling up' goals. An alternative to net neutrality is net diversity: allowing ISPs to decide how they operate their networks for their customers; enabling greater experimentation in product offerings and business models; and allowing ISPs to reach deals with large content providers to enable more investment in infrastructure. The possibility of ISPs adopting differing practices would allow for greater competition, innovation and the discovery of the approach most beneficial to consumers. Divergence from EU rules is supported by ISPs including BT, Three and Virgin Media/O2 while content providers such as Google, Amazon and Netflix have opposed reform and, in particular, being forced to pay ISPs for access to users. Net neutrality advocates object that its abandonment could lead to anticompetitive behaviour by ISPs, such as blocking or slowing content or overcharging for faster access. Ordinary competitive pressures should be expected to prevent such behaviour, and if that fails, it could be controlled by ex post competition enforcement by Ofcom and the CMA. There is no requirement for ex ante net neutrality regulation. Ofcom is reviewing the UK's net neutrality framework in response to growing internet demand, new technologies and congestion-sensitive applications that may justify prioritisation. Although Ofcom has proposed new guidance, the underlying rules are a matter for the government and Parliament. Innovation, investment and consumer interest would be served by a substantial abandonment of net neutrality regulations.
Keywords: 330